BLOQUEIO PERIDURAL E TERMOMETRIA CUTANEA COMO CRITERIO PARA INDICACAO CIRURGICA DE SIMPATECTOMIA LOMBAR - Lastoria, S.; Vianna, Pedro Thadeu Galvão [UNESP]; Yoshida, Winston Bonetti [UNESP]; Maffei, Francisco Humberto de Abreu [UNESP] (My University, 1977)
To find a valuable tool in achieving a good accuracy in predicting the outcome from sympathectomy, changes in limb skin temperatures (LST) before and after epidural lumbar anesthesia (ELA) and before and after lumbar sympathectomy were studied in 13 patients with thrombangiitis obliterans or arteriosclerosis obliterans. The results were compared with the clinical course and follow-up from 1 to 5 years. In seven patients there was a rise in LST after ELA and after sympathectomy, and this pattern of variation was associated with good clinical course. In three patients there was decrease in the LST after ELA and after sympathectomy and they did not do well. In two patients there was no change in temperature before or after the procedure; one of them had a good and the other a bad clinical course. The same measurements were performed in three other patients who had had a sympathectomy some years previously and the data showed that LST was lowered after ELA. It is concluded that the measurement of limb skin temperature before and after epidural lumbar anesthesia aids in determining which patients are more likely to benefit from sympathectomy.
Peridural blockage as a test for surgical sympathectomy
Keywords: autonomic nervous system; cardiovascular system; diagnosis; epidural anesthesia; major clinical study; preoperative evaluation; sympathectomy; therapy